2019
DOI: 10.3390/biom9090478
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antioxidant and Cytotoxic Activities of Extracts of Dendrobium crepidatum

Abstract: Dendrobium crepidatum is an epiphytic orchid found in south Asia including Nepal and China. This orchid species is widely used in traditional Chinese medicine (TCM) for the treatment of cancer, diabetes, cataracts, and fever. The objectives of the present research were to assess the antioxidant and cytotoxic properties of its stem’s extracts with the identification of bioactive secondary metabolites. The antioxidant and cytotoxic activities were evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) and MTT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 46 publications
(53 reference statements)
2
33
0
Order By: Relevance
“…The chemical compound isolated from the stem of Dendrobium chryseum exhibited antioxidant activity (Yang et al, 2007) and pharmacological experiments showed that polysaccharides from the plant inhibited tumor growth and reduced blood glucose in vivo (Liu et al, 2009). As the species of Dendrobium such as Dendrobium longicornu and Dendrobium crepidatum were found to exhibit antioxidant and cytotoxic activities (Paudel et al, 2017;Paudel et al, 2019), it is expected to have the same type of activities in D. chryseum. As this orchid species has great significance in the floriculture industry and also has medicinal value, tissue culture should be promoted for its mass propagation and conservation.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical compound isolated from the stem of Dendrobium chryseum exhibited antioxidant activity (Yang et al, 2007) and pharmacological experiments showed that polysaccharides from the plant inhibited tumor growth and reduced blood glucose in vivo (Liu et al, 2009). As the species of Dendrobium such as Dendrobium longicornu and Dendrobium crepidatum were found to exhibit antioxidant and cytotoxic activities (Paudel et al, 2017;Paudel et al, 2019), it is expected to have the same type of activities in D. chryseum. As this orchid species has great significance in the floriculture industry and also has medicinal value, tissue culture should be promoted for its mass propagation and conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant effect of the extract was determined using a DPPH (2,2-diphenyl-1-picrylhydrazyl) free-radical scavenging assay [ 24 ]. The extract was diluted in methanol to prepare a series of concentrations (125, 250, 500 and 1000 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Anticancer effect of the extract toward human cervical cancer (HeLa) and brain tumour (U251) cell lines was determined using MTT colourimetric assay [ 24 ]. From the cell suspension, 5 × 10 3 cells in 100 μl of RPMI-1640 medium supplemented with l -glutamine, penicillin/streptomycin and 10 % fetal bovine serum (FBS) were dispensed into the well of a 96-well cell culture plate and incubated under the cell culture conditions at 37 °C and 5% CO 2 for 48 h to allow for adherence and growth of cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, orchid species have been cultured with various techniques to synthesize bioactive molecules in vitro [ 34 , 35 ]. In the present study, D. chryseum was cultured in vitro to produce protocorms for the assessment of potential cytotoxic activity and comparison of such activities with its wild counterparts.…”
Section: Introductionmentioning
confidence: 99%